Engaging dissonance : developing mindful global citizenship in higher education - Lee, Amy; Williams, Rhiannon D. (Emerald Publishing, 2017)
This volume explores the internationalization of higher education in the context of global citizenry and intercultural competencies. It focuses on presenting dissonance as a means to facilitating students' openness to complexity and development of intercultural skills or their experiences in the classroom.
Keywords: International education.; Education and globalization.; Education, Higher.; elektronické knihy; electronic books